THE EFFECT OF HYPNOSIS THERAPY ON SLEEP DISORDER IN MENOPAUSAL AND POSTPARTUM WOMEN: A LITERATURE REVIEW - Taqiyya, Nadia; Rizki, Mutiara Putri Nanda Rizki; Zhafirah, Lina; Diarsy, Amina; Nafiati, Dini Latifatun (Journal of Psychiatry Psychology and Behavioral Research, 2025)
Introduction: Menopause is a normal phase in a woman's life marked by the discontinuation of menstruation due to hormonal changes, often accompanied by sleep disturbances. These sleep disturbances can negatively impact health and well-being. The global prevalence of sleep disturbances among postmenopausal women is quite significant. Several studies have shown that hypnosis therapy can improve sleep quality in menopausal and postmenopausal women. This review aims to evaluate the effects and benefits of hypnosis therapy on sleep disturbances in menopausal and postmenopausal women through a literature review. We also analyze how various media are used in hypnosis therapy interventions. Methods: This study uses a literature review method by accessing relevant articles through electronic databases such as PubMed, Science Direct, and Google Scholar, focusing on publications from the last 10 years. Inclusion and exclusion criteria were applied in selecting the articles. Results: Five studies were analyzed, showing that hypnosis therapy using various research methods and types of hypnosis effectively addresses sleep disturbances in menopausal and postmenopausal women. Discuss: Hypnotherapy teletherapy could become a standard form of therapy globally, though there may still be a necessity for traditional face-to-face therapy based on patient preference.11 Teletherapy hypnosis can improve sleep quality by targeting psychological mechanisms such as pre-sleep arousal and reducing worry, paving the way for more effective interventions. Conclusion: The results indicate that different research methods and media types used for hypnosis therapy in the sample show consistent results that hypnosis therapy positively affects reducing sleep disturbances in menopausal and postmenopausal women.